2015
DOI: 10.1016/j.ijgo.2015.04.043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal betamethasone on fetal, uteroplacental, and maternal blood flow velocity in pregnancies complicated by fetal growth restriction

Abstract: Prenatal betamethasone led to transient improvements in blood flow in the uterine and umbilical arteries among pregnancies affected by FGR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Concordant with the literature, the uterine artery Doppler indices remained unchanged after betamethasone administration, indicating that betamethasone did not affect the uterine blood flow. Niroomanesh et al . reported transient changes in Doppler indices of the uterine artery among pregnancies affected by fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concordant with the literature, the uterine artery Doppler indices remained unchanged after betamethasone administration, indicating that betamethasone did not affect the uterine blood flow. Niroomanesh et al . reported transient changes in Doppler indices of the uterine artery among pregnancies affected by fetal growth restriction.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 In some pregnancies, steroid administration has been shown to result in placental vasodilatation, resulting in the temporary improvement of impaired fetoplacental blood flow; however, betamethasone administration has not been reported to cause any change in the fetoplacental vessels of fetuses with severe growth restriction. [5][6][7] Other studies have evaluated the effects of steroids on the biophysical profile; these studies have revealed reductions in fetal movement, breathing, or amniotic fluid index (AFI), resulting in decreased biophysical profile scores. 8,9 The present study investigated the unanticipated effects of betamethasone on fetomaternal blood flow and AFI.…”
Section: Introductionmentioning
confidence: 99%
“…Further, betamethasone and dexamethasone are potent drugs, which cross through the placenta and reach the fetus 2-3 hours after administration (7). Similarly, corticosteroid administration promotes surfactant secretions and increases fetal lung maturity (19). The results of various studies have shown that the administration of these two corticosteroids significantly reduces death, RDS, IVH, NEC, and PDA during pregnancy (15 (21).…”
Section: Discussionmentioning
confidence: 99%
“…19 In a 2009 review of the literature, Torrance et al concluded that the effect of ACS on neonatal outcomes of intrauterine growth restricted (IUGR) fetuses remains inconclusive, and IUGR fetuses with abnormal umbilical artery Doppler studies treated with ACS did not have a significant alteration in the incidence of RDS, IVH, NEC, or neonatal mortality. 20 In IUGR fetuses with abnormal umbilical artery Doppler blood flow, some studies have demonstrated a transient improvement in the umbilical artery Doppler blood flow, [21][22][23][24] while others have not. 25,26 This divergence in effect has caused some to hypothesize that IUGR fetuses without a transient improvement in umbilical artery Doppler flow may be at a higher risk for perinatal complications and hemodynamic decompensation after ACS administration.…”
Section: Fetal Growth Restrictionmentioning
confidence: 99%